Implementasi Plugin Metode Penilaian Otomatis UTS dan UAS pada Mata Kuliah - Akbar, Muhammad Nur; Meidinah, Nur; Nur Hidayat, Andi Muhammad (Prodi Sistem Informasi UIN Alauddin, 2023)
The era of the 4.0 industrial revolution, as it is today, is developing rapidly in the field of technology in various countries, including Indonesia itself. Nowadays, there is a lot of technological sophistication that supports the development of the information world. However, some teachers still rely on manual evaluation in the learning process. The lack of implementation of technological advances of course makes the assessment process inefficient. The method of automatic valuation is a solution that can be used to deal with the problem. By applying e-learning technology, the process of digitization will be faster. In this research, that is the main focus is the exam. Moodle as an e-Learning technology has many features that can be applied, one of which features automatic evaluation. With the implementation of automated assessment, the assessment process for mid-term and end-term exams becomes more efficient and effective. Automatic evaluations tend to provide more accurate and consistent results, eliminating the potential for human error in the evaluation process, so students get feedback faster after completing the quiz, which can help them understand and improve their understanding.